Determinants of Maternal Behavior in Measles Prevention in Children Aged Toddlers in Banda Aceh City 2023 - Sofaa Rihadah; Farrah Fahdhienie; Vera Nazhira Arifin (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Measles or Mealses Rubella (MR) is an infectious disease caused by a virus and is easily transmitted. Measles cases at the Lampaseh Health Center always increase every year. In 2022, the most measles cases reached 70 cases and in 2023 measles cases at the Lampaseh Health Center reached 23 cases. Objective: This study aims to identify determinants of maternal behavior in the prevention of measles in children aged toddlers (1-5 years) in the working area of the Lampaseh Health Center. Method: This study used analytical observational method with a cross-sectional approach. The population in this study is mothers registered in the posyandu registration book in six villages in the working area of the Lampaseh Health Center. Sampling with a simple random sampling technique amounted to 90 mothers who had toddlers. Data collection was conducted by interviews using questionnaires. Data analysis using chi-square test and logistic regression test using SPSS 22 program. Result: The results of the study based on univariate analysis showed mothers who had good behavior in measles prevention 60.0%, the highest education category was the middle category 56.7%, mothers the most as IRT 62.2%, families with high income 55.6%, mothers who had information sources 73.3%, mothers whose families were less supportive 51.1% and mothers with health workers played a role 55.6%. The results of bivariate analysis showed that there was a relationship between education levels (P-Value = 0.039), family income (P-Value = 0.009), information sources (P-Value = 0.001), family support (P-Value = 0.001) and the role of health workers (P-Value = 0.001) with maternal behavior in measles prevention in children under five years old. Multivariate test results obtained that family support (P-Value = 0.001; OR = 10.206) and the role of health workers (P-Value = 0.005; OR = 5.942). Conclusion: There is a relationship between maternal education, family income, sources of information, family support and the role of health workers and maternal behavior in measles prevention in children under five years old.